2013
DOI: 10.1148/radiol.12120414
|View full text |Cite
|
Sign up to set email alerts
|

Reduced-Dose Low-Voltage Chest CT Angiography with Sinogram-affirmed Iterative Reconstruction versus Standard-Dose Filtered Back Projection

Abstract: http://radiology.rsna.org/lookup/suppl/doi:10.1148/radiol.12120414/-/DC1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
64
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(65 citation statements)
references
References 21 publications
(4 reference statements)
1
64
0
Order By: Relevance
“…Similarly, Winklehner et al 19 showed the potential to reduce the radiation dose by Ͼ50% in body CTA studies by using SAFIRE without a deterioration in image quality. In a chest CT study, Pontana et al 16 demonstrated a 50% lower dose while image quality was preserved. SAFIRE has also been recently applied in the study of cervical spine CT, providing better image quality for intervertebral disks, the neural foramina, and ligaments compared with FBP, while reducing the radiation dose by approximately 40%.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Similarly, Winklehner et al 19 showed the potential to reduce the radiation dose by Ͼ50% in body CTA studies by using SAFIRE without a deterioration in image quality. In a chest CT study, Pontana et al 16 demonstrated a 50% lower dose while image quality was preserved. SAFIRE has also been recently applied in the study of cervical spine CT, providing better image quality for intervertebral disks, the neural foramina, and ligaments compared with FBP, while reducing the radiation dose by approximately 40%.…”
Section: Discussionmentioning
confidence: 98%
“…In the literature, there is a wide variation of dose-reduction results by using SAFIRE, [15][16][17][18][19][20][21] which makes it difficult to compare results. Differences might be partially explained by the inconsistency FIG 1. Boxplot diagrams.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Even for pulmonary GGNs, previous studies using simulated pulmonary nodules demonstrated that CDT had detection sensitivities (DSs) superior to those of chest radiography irrespective of nodular size 11 and was comparable to those of low-dose CT (LDCT) in relatively less attenuated nodules. 12 For CT images scanned at reduced or low dose, which actually varied from 50% to 80% in reduction rate based on the radiation dose level adopted in standard-dose CT images, [13][14][15] IR algorithms [16][17][18][19][20][21] can provide noise-reduced images based on different assumptions for noise recognition in image generation with the standard filtered back projection (FBP) algorithm. 22,23 These reconstruction algorithms have recently been applied to breast digital tomosynthesis 24 and are expected to improve the detectability of subtle pulmonary abnormalities such as GGN.…”
Section: Introductionmentioning
confidence: 99%
“…Individually, each has been studied intensively before leading to the clinical application [3][4][5][6][7][8][9][10] . Lower tube voltage can provide better contrast because iodine preferentially absorbs much more photons at low tube voltage, but at lower tube voltage, images can be undesirably noisy [8][9][10][11] . Iterative reconstructions have been proven to reduce radiation dose notably, but can also alter the noise texture and obscure potential lesions of interest against a "waxy appearance" [5,7,11,12] .…”
Section: Introductionmentioning
confidence: 99%